An innovation policy framework for upgrading firm absorptive capacities in the context of catching-up economies - Agnė Paliokaitė (Journal of Entrepreneurship, Management and Innovation)
The paper addresses the ‘regional innovation paradox’ referring to the lower capacity to absorb public funds earmarked for the promotion of innovation in the peripheral regions. The key aim is thus to propose and test a conceptual framework of tailored innovation policy routes that aim at stimulating absorptive capacities of firms. Literature analysis helps to distill determinants of absorptive capacity at firm and system levels. Analysis of innovation policies applied by the Central and Eastern European (CEE) countries in 2007-2013 is used to determine the gap between mainstream innovation policies and business capacity building needs. The paper presents an integrative conceptual ‘stairway of competence’ framework, mapping four innovator types with alternative policy routes. An assessment of innovation policies in the selected CEE countries is provided. We find that mainstream innovation policies in the selected countries mainly focused on two routes: strengthening the capacities of mature innovators and the uptake of existing technology. There is little evidence that this approach had any clear effects on structural change in the CEE economies. These findings suggest that a more tailor-made approach to innovation capacity building is needed, taking into account the current capacity levels within the target groups. These findings are especially relevant to the use of European Union cohesion policy funds and the implementation of the smart specialization strategies. Although the CEE is the main context for the framework, its implications are applicable to other catching-up and peripheral regions more widely